Calcule en détaillant toutes les étapes:

A= -2 - 3 x 5 - 7=

B= -2 - 3 x (5 - 7)=

C= (-2 - 3) x 5 - 7=

Calculer les expressions suivantes pour a= -2 , b= +6 et c= -2:

A= 2b + 3a - 2=

B= (2b + c)(a-2)=

C= 2(b + 3)a-2=

D= a +

AIDER MOI S.V.P

2

Réponses

2012-10-30T20:41:00+01:00

A= -2 - 3 x 5 - 7=-2-15-7=-24

B= -2 - 3 x (5 - 7)=-5*-2=10

C= (-2 - 3) x 5 - 7=-5*5-7=25-7=18

 

A= 2b + 3a - 2=12+(-6)-2=12-6-2=12-8=4

B= (2b + c)(a-2)=(12+(-2))(-2-2)=10*-4=-40

C= 2(b + 3)a-2=2(6+3)*-2-2=18*(-2)-2=-36-2=-38

D= a +  je ne peux la résoudre

bonne chance

2012-10-30T20:41:59+01:00

A=-2-15-7=13-7=6

B=-2-15-7=13-7=6

C=-2-15-7=13-7=6

A=12-6-2=4

B=(12+2)(-2-2)=40x-4=-40

C=2(6+3)-2-2=18-4=14

D=-2+